PERTANGGUNGJAWABAN NOTARIS YANG MENERBITKAN AKTA BERISI KETERANGAN PALSU (STUDI KASUS PERKARA NOMOR 1362/PID.B/2019/PN.JKT.UTR) - Bella Annisa Ardhani; Busyra Azheri (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
A notary is a public official authorized to make authentic deeds. This authority must be carried out in accordance with the regulations stipulated in the Notary Office Act and not violate the Notary Code of Ethics. However, not a few notaries carry out their duties in accordance with the established regulations, resulting in a party being harmed and the notary being held accountable. This happened in the Decision on Criminal Case Number 1362/Pid.B/2019/Pn.Jkt.Utr. In this decision, notary R forged an authentic deed because he entered information that was not in accordance with the facts and also did not read and sign the deed he made in front of the parties. Therefore, this thesis takes the title Liability of a Notary Who Issues Deeds Containing False Statements (Case Study Case Number 1362/Pid.B/2019/PN.Jkt.Utr). The formulation of the problem in this research is: 1) What are the legal considerations of the judges in deciding case number 1362/Pid.B/2019/PN.Jkt.Utr? 2) What is the responsibility of the notary for the deed he made based on case number 1362/Pid.B/2019/PN.Jkt.Utr? This study uses normative juridical legal research methods, namely the systematic compilation of data, assessment, then concludes on the relationship to the problems studied with the statutory approach. The results of this study are: 1) The basis for the judge's consideration in decision number 1362/Pid.B/2019/PN.Jkt.Utr comes from juridical and non-juridical and grants the indictment of the public prosecutor in accordance with the provisions violated by notary R but the judge does not make the existence of peace into the lightening thing. 2) The responsibility imposed on notary R is administrative sanctions, namely temporary dismissal due to being in custody then the main sanction is imprisonment for 1 (one) year and 8 (eight) months.